A Meta-Analysis Comparing Postoperative Complications and Outcomes of Femtosecond Laser-Assisted Cataract Surgery versus Conventional Phacoemulsification for Cataract - Zi Ye; Zhaohui Li; Shouzhi He (Journal of Ophthalmology)
Objective. This meta-analysis aimed to compare the outcomes and postoperative complications between femtosecond laser-assisted cataract surgery (FLACS) and conventional phacoemulsification cataract surgery (CPCS). Methods. Bibliographic databases, including PubMed, Embase, and Cochrane library, were systematically searched for references on or before September 2015 regarding the outcomes and complications by FLACS or CPCS. Data on corneal endothelial cell loss, uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), refractive outcomes, and postoperative complications were retrieved. Results. A total of 9 trials were included in this analysis. Refractive outcomes (MD = −0.21, 95% CI: −0.39~0.03, P=0.02) were significantly improved after FLACS. Although corneal endothelial cell loss was not significantly reduced after FLACS, there was a trend towards lower corneal endothelial cell loss (mean difference (MD) = 197.82, 95% confidence interval (CI): 2.66~392.97, P=0.05) after FLACS. There was no significant difference in UDVA (MD = −0.01, 95% CI: −0.13~0.10, P=0.80) or CDVA (MD = −0.03, 95% CI: 0.07~0.00, P=0.09) between the two surgeries. Elevated intraocular pressure and macular edema were most commonly developed complications after cataract surgery, and the incidence of these complications associated with the two surgeries was similar. Conclusion. Compared with CPCS, FLACS might achieve higher refractive stability and corneal endothelial cell count. Nevertheless, further study is needed to validate our findings.